In vivo hypoglycemic and anti-diabetic study of Oncocalyx glabratus (Bangladesh Journal of Pharmacology, 2015)
The present study was designed to investigate the hypoglycemic and anti-diabetic potential of Oncocalyx glabratus. The extracts and fractions of plant were administrated orally to mice at a dose of 400 mg/kg. The hypoglycemic effect, glucose tolerance test and lipid profile were assessed in treated mice, compared with normal, diabetic and standard drug treated mice. In the hypoglycemic and anti-diabetic study the extracts and fraction reduced blood glucose level and achieved the significant value (p